2017
DOI: 10.1002/aenm.201701261
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Catalytic Carbon Nanotemplates for Sodium Metal Anodes

Abstract: Lithium and sodium metal have recently have been proposed as alternative negative electrode materials because of their low redox potentials (−3.04 and −2.71 V vs the standard hydrogen electrode, respectively) and high theoretical capacities (3860 and 1166 mA h g −1 , respectively) which are 10 and 3 times higher, respectively, than that (372 mA h g −1 ) of a graphite anode in a typical Li ion battery. [15,16] Nevertheless, these metal anodes have fatal problems such as low Coulombic efficiencies, infinite volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 57 publications
0
74
0
Order By: Relevance
“…In our previous studies, it was found that BC pellicles can be carbonized by simple heating with maintaining its intrinsic pore structure [14,16,17]. And the carbonized BC pellicles were graphitized with further high-temperature heating by 2400°C [17]. Moreover, the carbonized/graphitized BC pellicles were free-standing, which can be used as an electrode material for energy storage without binder and substrate [14,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, it was found that BC pellicles can be carbonized by simple heating with maintaining its intrinsic pore structure [14,16,17]. And the carbonized BC pellicles were graphitized with further high-temperature heating by 2400°C [17]. Moreover, the carbonized/graphitized BC pellicles were free-standing, which can be used as an electrode material for energy storage without binder and substrate [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…BC has a unique pore structure and properties compared to other types of cellulose in terms of its purity, high crystallinity, and high mechanical strength [15]. In our previous studies, it was found that BC pellicles can be carbonized by simple heating with maintaining its intrinsic pore structure [14,16,17]. And the carbonized BC pellicles were graphitized with further high-temperature heating by 2400°C [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the price issue, sodium metal batteries (SMBs) based on abundant and ubiquitous sodium resources appear to be more suitable. Despite the apparent suitability, SMBs suffer from technological barriers similar to LMBs, which are induced by dendritic metal growth and mossy metal deposits . Therefore, several studies have been conducted to find a means to control undesirable metal growth .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was confirmed that an ether‐based electrolyte system and/or additives can induce dendrite‐free cycling . Under an ether‐based electrolyte, the lithiophilic/sodiophilic sites of carbon‐based catalytic material (CCM) guide homogeneous metal nucleation, resulting in improved cycling performance . More functionalized CCMs, including a large number of catalytic sites, exhibited more efficient metal deposition/striping behaviors, leading to feasible electrochemical performance corresponding to a CE value of ≈99.9%.…”
Section: Introductionmentioning
confidence: 99%